2022
DOI: 10.3389/fimmu.2022.842535
|View full text |Cite
|
Sign up to set email alerts
|

New Discovery of Myeloid-Derived Suppressor Cell’s Tale on Viral Infection and COVID-19

Abstract: Myeloid-derived suppressor cells (MDSCs) are generated under biological stress such as cancer, inflammatory tissue damage, and viral infection. In recent years, with occurrence of global infectious diseases, new discovery on MDSCs functions has been significantly expanded during viral infection and COVID-19. For a successful viral infection, pathogens viruses develop immune evasion strategies to avoid immune recognition. Numerous viruses induce the differentiation and expansion of MDSCs in order to suppress ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…Normally, bone marrow cells differentiate into various immune cells, such as granulocytes, monocyte-macrophages, or dendritic cells. However, in the presence of inflammation, tumors, trauma, or other pathological states, this differentiation is halted, leading to the formation of MDSCs ( 201 ). These cells are categorized into two primary types in both humans and mice, based on their lineage: granulocytic/polymorphonuclear MDSCs (PMN-MDSCs) and monocytic MDSCs (M-MDSCs) ( 202 ).…”
Section: New Immunotherapiesmentioning
confidence: 99%
“…Normally, bone marrow cells differentiate into various immune cells, such as granulocytes, monocyte-macrophages, or dendritic cells. However, in the presence of inflammation, tumors, trauma, or other pathological states, this differentiation is halted, leading to the formation of MDSCs ( 201 ). These cells are categorized into two primary types in both humans and mice, based on their lineage: granulocytic/polymorphonuclear MDSCs (PMN-MDSCs) and monocytic MDSCs (M-MDSCs) ( 202 ).…”
Section: New Immunotherapiesmentioning
confidence: 99%
“…Several studies have also reported elevated numbers of MDSCs in patients with chronic HIV infection, which dampen anti-HIV T-cell-mediated immune responses ( 152 , 153 ) and promote the development of Tregs ( 154 ). An increased frequency of MDSCs has been observed in the peripheral blood of patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), particularly those with severe disease ( 155 ). The expansion of MDSCs in SARS-CoV-2-infected patients appears to correlate with the severity of respiratory symptoms and the need for intensive care ( 155 ).…”
Section: Suppressive Mechanisms Of Mdscsmentioning
confidence: 99%
“…An increased frequency of MDSCs has been observed in the peripheral blood of patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), particularly those with severe disease ( 155 ). The expansion of MDSCs in SARS-CoV-2-infected patients appears to correlate with the severity of respiratory symptoms and the need for intensive care ( 155 ).…”
Section: Suppressive Mechanisms Of Mdscsmentioning
confidence: 99%
“…It can be seen that M-MDSCs not only suppress the immune activity of T cells during the acute episode after SARS-CoV-2 infection, but also have a recall response to suppress T cells during the recovery period. In conclusion, the results of different studies may vary, but MDSCs exhibit different phenotypic characteristics and functional status with various stages of COVID-19, and MDSCs, as one of the key pathogenic factors of COVID-19 inflammation and immunosuppression, may be a major target for treatment ( 30 , 46 , 47 ).…”
Section: Mdscs As a Target For Infectious Lung Diseasesmentioning
confidence: 99%